2021
DOI: 10.1021/acschembio.1c00106
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Class I Lanthipeptides from Pedobacter lusitanus NL19 Reveals an Unusual Ring Pattern

Abstract: Lanthipeptides are ribosomally synthesized and post-translationally modified peptide natural products characterized by the presence of lanthionine and methyllanthionine crosslinked amino acids formed by dehydration of Ser/Thr residues followed by conjugate addition of Cys to the resulting dehydroamino acids. Class I lanthipeptide dehydratases utilize glutamyl-tRNA Glu as a cosubstrate to glutamylate Ser/Thr followed by glutamate elimination. A vast majority of lanthipeptides identified from class I synthase sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 87 publications
2
60
0
Order By: Relevance
“… 9 More recent additional examples of the ll -(Me)Lan stereochemistry were identified in class I lanthipeptides where the conserved Dhb-Dhx-Xxx-Xxx-Cys motif was absent suggesting that anti- addition to the Re -face is more common than previously thought. 7 , 8 …”
Section: Discussionmentioning
confidence: 99%
“… 9 More recent additional examples of the ll -(Me)Lan stereochemistry were identified in class I lanthipeptides where the conserved Dhb-Dhx-Xxx-Xxx-Cys motif was absent suggesting that anti- addition to the Re -face is more common than previously thought. 7 , 8 …”
Section: Discussionmentioning
confidence: 99%
“…And no clear conserved motif was found among leader peptides of similar peptides except for Lys rich region (2nd-11th amino acids). In the previous report (Bothwell et al, 2021), Lys rich region in the leader peptide was reported in the biosynthesis of a class I lanthipeptide PedA15.1. We proposed that this Lys rich region may be the modification enzyme recognition motif of this group of class I lanthipeptides.…”
Section: Discussionmentioning
confidence: 90%
“…Glutamyl residue is provided from glutamyl tRNA (tRNA-Glu). In the case of heterologous production of class I lanthipeptide, tRNA-Glu and glutamyl tRNA synthase (GluRS) are required from the same bacterium which have the dehydratase (LanB) because lanthionine dehydratase (LanB) is indicated to recognize specific tRNA-Glu of same bacterial origin (Bothwell et al, 2021;Hudson et al, 2015;Ozaki et al, 2016). In this report, we F I G U R E 3 Proposed biosynthetic pathway for thalassomonasin A, underlined sequence is Lys rich region possibly recognized by modification enzymes observed production of class I lanthipeptides thalassomonasins A and B without introducing tRNA-Glu and GluRS of T. actiniarum into the co-expression system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations